HYDROXYMETHYL FURFURAL IN CHINESE HERBAL MEDICINES: ITS FORMATION, PRESENCE, METABOLISM, BIOACTIVITIES AND IMPLICATIONS - Gao, Hui-feng; Wen, Xue-sen; Xian, Cory J. (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Hydroxymethyl furfural (HMF) is one of important intermediates formed in Maillard reaction and caramelization. It was found that HMF existed in many Chinese herbal medicines (CHMs) and accumulated during CHM processing. In recent years, increasing attention has been paid to its safety and actions in CHMs, which has led to many reports about different aspects of HMF. In this paper, previous and recent studies on HMF formation, its presence in CHMs, its metabolism and bioactivities, together with its implications for CHMs were summarized, with the purpose of contributing to a better understanding of CHMs.